Religious Values in Geguritan Sang Cangak - I Made Luwih (Jayapangus Press, 2021)
The study aimed to determine religious education values contains in Geguritan Sang Cangak. This study was qualitative with data collection using the library and document methods. The data analysis method used a descriptive method and checking the data validity. Based on the analysis results, it could see that Sang Cangak is the title of Gaguritan and the main character in Gaguritan. In terms of behavior, the author describes a character who full of cunning, lies, and is good at keeping rotten. The other Sang Congak’s nature is uncommendable things. Throw the stone and hide the hands. The badness inside wrapped up neatly in the goodness outside. In the end, Sang Congak got his karma. The character description can provide an overview for students about the existence of the law of karmaphala. All deeds have consequences, either good or bad. Also, which deeds are good to follow and not to imitating.